NEW GENUS OF HETEROSPOROUS FERNS OF THE ORDER HEROLEANDRALES FROM THE LOWER CRETACEOUS OF KAZAKHSTAN - Golovneva L.B.; Krassilov V.A. (My University, 2001)
As a result of a study of spore-bearing structures, a new genus, Vachramelia, is established for a fern from the Lower Cretaceous of Kazakhstan previously described as Adiantites prigorovskii Vachr. (Vachrameev, 1952). The genus is assigned to the recently discovered order Heroleandrales that includes heterosporous plants with solitary sporangia producing numerous megaspores and with four megaspore tetrad members equally developed (Krassilov and Golovneva, 2000). The new find adds to knowledge of the morphology and extends the stratigraphie range of the order.
Keywords: Cretaceous; Kazakhstan; Heroleandrales; Мезозой::Меловая; Mesozoic::Cretaceous